THE IMAGE OF A SCHIZOID CHARACTER IN M. MAGAUIN'S NOVEL "ZHARMAK" AND "SCHIZOPHRENIC DISCOURSE" (BULLETIN OF SHAKARIM UNIVERSITY PHILOLOGY SERIES SCIENTIFIC JOURNAL, 2026)
The article examines the image of a schizoid character in M. Magauin's novel «Zharmak» within the framework of schizophrenic discourse. The purpose of the article is to identify the artistic representation of the phenomena of personality splitting, inner self, spontaneity, and intellectualization in the work and to determine their narrative structure. The research uses the methods of narratological, discursive, and content analysis. At the same time, the frequency and stability of schizoid signs in the text are assessed using both qualitative and quantitative approaches.As a result of the study, it was found that the image of a schizoid character in the novel is realized not only in a psychological state, but also through a narrative structure, fragmentary narration, internal monologue, and subjectivation of time and reality. At the same time, existential questions about the limits of human existence in a "painful civilization" were not ignored. The dual confrontation of the novel's main characters, Murat and Marat, was justified as a conceptual model reflecting the split of personality, the crisis of values in modern society, and the internal conflict of consciousness.The scientific significance of the study is determined by a comprehensive theoretical study of the schizoid nature and «schizophrenic discourse» in Kazakh literature. It has practical value in teaching problems of literary criticism, narratology, and psychological prose, as well as in interpreting modern Kazakh prose. The results of the study can serve as a basis for a comprehensive study of marginal consciousness in the art of speech and in the practice of teaching modern Kazakh literature.